1990
DOI: 10.1007/bf00705037
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response in the forearm during and after isometric intermittent handgrip

Abstract: The aim of the present paper was to study the development of fatigue during isometric intermittent handgrip exercise. Using a handgrip dynamometer, four combinations of contraction-relaxation periods were studied (10 + 10, 10 + 5, 10 + 2 s and continuous contraction) at three contraction intensities (10, 25 and 40% maximum voluntary contraction, MVC). Local blood flow (BF) in the forearm (venous occlusion plethysmography) was followed before, during and after the exercise period. Electromyography (EMG) (freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(58 citation statements)
references
References 29 publications
5
50
0
3
Order By: Relevance
“…The observation that partial obstruction of blood flow occurs at intramuscular pressure levels well below blood pressure is supported by studies that investigated tissue oxygenation [102] and hyper-compensation in blood flow post-exercise [20,21,57,58,113]. For example, Jensen et al [58] found post-exercise hyperaemia values of two times the resting blood flow even after isometric handgrip exercise at an intensity as low as 2.5% MVC and Røe and Knardahl [113] found such hyperaemia after computer work.…”
Section: Impaired Blood Flowmentioning
confidence: 86%
“…The observation that partial obstruction of blood flow occurs at intramuscular pressure levels well below blood pressure is supported by studies that investigated tissue oxygenation [102] and hyper-compensation in blood flow post-exercise [20,21,57,58,113]. For example, Jensen et al [58] found post-exercise hyperaemia values of two times the resting blood flow even after isometric handgrip exercise at an intensity as low as 2.5% MVC and Røe and Knardahl [113] found such hyperaemia after computer work.…”
Section: Impaired Blood Flowmentioning
confidence: 86%
“…a decrease in the force generating capacity of the muscle, Fallentin et al, 1985;Krogh-Lund, 1993), does develop, accompanied by electromyographic manifestations of fatigue Byströ m and Kilbom, 1990;Fallentin et al, 1985;Krogh-Lund, 1993), as well as subjective experiences of fatigue (Byströ m and Kilbom, 1990;Sjøgaard et al, 1986). Evidence on fatigue development in low-level activity was, however, obtained in muscles of the extremities, not habitually exposed to sustained activity.…”
Section: Introductionmentioning
confidence: 82%
“…The possible increase of non-nutritive perfusion (Kalliokoski et al 2003) and/or mismatch in oxygen demand and oxygen supply (Walley 1996) may be the two possible reasons. During isometric exercise of 30-70% MVC, there was reduced and/or occluded blood Xow through the exercising muscles (Bystrom and Kilbom 1990;Humphreys and Lind 1963;Larsson et al 1996;Sjogaard et al 1988). The result is a closed system, which is mostly dependent on the capacity of the local anaerobic energy processes.…”
Section: Discussionmentioning
confidence: 96%